IMPLEMENTASI KINERJA PEMASARAN DALAM MENINGKATKAN PERTUMBUHAN NASABAH PRODUK REKENING TABUNGAN JAMAAH HAJI - Octavia, Ika; Sunaryo (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2022)
The objective of this research is to identify the application of marketing performance in increasing the number of clients of Rekening Tabungan Jamaah Haji (RTJH, a saving product for customers who plan to do Hajj pilgrimage) at the Sharia-Compliant Business Unit of Bank Sinarmas in the branch office of Malang. Here supporting factors, hindering factors, and strategies in the banks effort to increase the number of clients are also examined. This descriptive qualitative case study uses primary and secondary data; the former was gathered from interviews and observations, while the latter was acquired from documents consisting of annual reports and other relevant information. This study finds that the marketing performance has been successfully implemented, proven by the increasing number of sales and clients as well as by the growing market. The said business unit is also proven able to analyze the supporting and hindering factors and to apply the appropriate marketing strategy using the marketing mix consisting of the Seven Ps. However, the unit has not been able to attain the maximum benefit of the mix, that is in the aspect of place, promotion, people, and physical evidence.